2015
DOI: 10.1002/eji.201444625
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effector B cells directly kill tumor cells via the Fas/FasL pathway and are regulated by IL‐10

Abstract: We have previously reported that adoptive transfer of tumor-draining lymph node (TDLN) B cells confers tumor regression in a spontaneous pulmonary metastasis mouse model of breast cancer. In this study, we identified IL-10-producing cells within these B cells, and found that IL-10 removal, either by using IL-10−/− TDLN B cells or by systemic neutralization of IL-10, significantly augmented the therapeutic efficacy of adoptively transferred TDLN B cells. Depletion of IL-10 in B-cell adoptive transfers significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 39 publications
(100 reference statements)
3
85
0
Order By: Relevance
“…Though they are meant to control the early stages of viral infection, infiltrating NK cells release perforin, which damages myocardial cells Lutz et al, 2014;Hsiao et al, 2015;Künkele et al, 2015;Peng et al, 2015). Between 7 and 14 days after the initial onset of the viral infection, most of the infiltrated cells are T-cells, which become CTLs when activated, and are programmed to kill target cells (Chen et al, 2014;Grygorczuk et al, 2015;Shi et al, 2015;Tao et al, 2015). There are two primary means by which CTLs kill target cells: one is perforin/granzyme-mediated and the other involves the Fas-FasL signaling pathway (Arai et al, 2014;Gmeiner et al, 2015;Liu et al, 2015;Nallapalle et al, 2015;O'Donnell et al, 2015;Saigusa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Though they are meant to control the early stages of viral infection, infiltrating NK cells release perforin, which damages myocardial cells Lutz et al, 2014;Hsiao et al, 2015;Künkele et al, 2015;Peng et al, 2015). Between 7 and 14 days after the initial onset of the viral infection, most of the infiltrated cells are T-cells, which become CTLs when activated, and are programmed to kill target cells (Chen et al, 2014;Grygorczuk et al, 2015;Shi et al, 2015;Tao et al, 2015). There are two primary means by which CTLs kill target cells: one is perforin/granzyme-mediated and the other involves the Fas-FasL signaling pathway (Arai et al, 2014;Gmeiner et al, 2015;Liu et al, 2015;Nallapalle et al, 2015;O'Donnell et al, 2015;Saigusa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of surface markers' characteristic of APC by tumor-infiltrating B cells was also described in primary lung cancer (Yasuda et al, 2002) and in hepatocellular carcinoma (Shi et al, 2013). Finally, few studies suggested that some tumorinfiltrating B cells could act as true killer cells, through the expression of granzyme B and TRAIL (Shi et al, 2013), or in a Fas Ligand-dependent manner (Tao et al, 2015).…”
Section: Role Of B Cellsmentioning
confidence: 95%
“…Subsequently, they verified IL‐10‐producing cells among these B cells. As a result, the antitumor efficacy could be significantly enhanced with adoptive transfer of IL‐10 (‐/‐) TDLN B cells or by removal of IL‐10 from mice in which IL‐10 has been neutralized with Abs . Further evidence supports that administration of IL‐2 or adoptively transferred of TDLN B cells expressing IL‐2R could enhance this therapeutic effect …”
Section: Cancer Immunotherapies By Targeting B Cellsmentioning
confidence: 99%
“…In addition to producing specific Abs, B cells are also antigen presenting cells (APCs) that are able to present foreign antigens to T cells in vivo through their surface immunoglobulins. Meanwhile, B cells have the ability to directly kill tumor cells through Fas/Fas‐ligand pathway . Moreover, the first indication that B cells may promote tumor growth came from studies that were conducted nearly 60 years ago, in which the absence of B cells impaired tumor development .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation